A new method for lithium-ion battery uniformity sorting based on internal criteria. (October 2019) - Lyu, Chao; Song, Yankong; Wang, Lixin; Li, Junfu; Zhang, Bin; Liu, Enhui
Abstract: Lithium-ion battery (LIB) uniformity has remarkable influence on the durability and safety of the battery pack. It is therefore important to assemble batteries with good consistency in a pack. This paper proposes a new LIB uniformity sorting method based on some internal criteria. Firstly, a simplified electrochemical model (EM) with parameter identification is introduced. Secondly, internal sorting criteria are selected from EM parameters according to their sensitivities and strength of correlation to aging. Thirdly, based on the proposed internal criteria and/or existing external criteria, four 4-series-connected LIB packs are assembled with cells being selected from 120 LiCoO2 /graphite 14500 type LIB candidates and sorted by fuzzy C-means (FCM) algorithm A series of cyclic aging experiments are conducted and the results demonstrate that the proposed method can significantly prolong the cycle life of the pack and guarantee good voltage and state of charge (SOC) uniformity when internal criteria are used to sort cells for packs.